-5a-5(1-4a)=-5+4a

Simple and best practice solution for -5a-5(1-4a)=-5+4a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5a-5(1-4a)=-5+4a equation:


Simplifying
-5a + -5(1 + -4a) = -5 + 4a
-5a + (1 * -5 + -4a * -5) = -5 + 4a
-5a + (-5 + 20a) = -5 + 4a

Reorder the terms:
-5 + -5a + 20a = -5 + 4a

Combine like terms: -5a + 20a = 15a
-5 + 15a = -5 + 4a

Add '5' to each side of the equation.
-5 + 5 + 15a = -5 + 5 + 4a

Combine like terms: -5 + 5 = 0
0 + 15a = -5 + 5 + 4a
15a = -5 + 5 + 4a

Combine like terms: -5 + 5 = 0
15a = 0 + 4a
15a = 4a

Solving
15a = 4a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-4a' to each side of the equation.
15a + -4a = 4a + -4a

Combine like terms: 15a + -4a = 11a
11a = 4a + -4a

Combine like terms: 4a + -4a = 0
11a = 0

Divide each side by '11'.
a = 0

Simplifying
a = 0

See similar equations:

| 2(4+x)=4x+3 | | 5x-16=4x+7 | | 4x+3x=6x-6 | | 57=3y | | 3y+1=28 | | 5x-20=2x+4 | | 5d-2=63 | | -0.06y+0.08(1100-y)=0.36 | | 4x+3x=6x | | -3x+9=2x-6 | | 9n-12=69 | | 3y+14=5 | | -6x-17=-4x+7 | | 8(x+2)=3x+5 | | -11*3=15+-6*3 | | 7.8p-18=2.6p-5 | | 3x+8x-40=48 | | 9(x-5)=8(x-1) | | -96+5x=-8x+86 | | 2x+2=x+56 | | -3n-4=-2-3n | | 12x+14y=112 | | D-8d+7= | | 5x+2-x=2(x+3) | | 5(3x+2)-4+2(-5x+4)-3+14+2(5x-1)-7(3x+2y)+5(4x+2y)+11(5x+3y)+4(12x+5y)= | | 28=(4+x)+x | | 178-5x=40x+18 | | 9-x=x | | 2(x-4)+4x=10 | | -x+-3=7 | | .75v-6=.75v-6 | | 2x2=3 |

Equations solver categories